Operation Tracer: British Secret Eyes in the Rock - Afifa Mehboob; Hafiza Sahar Saeed (Social Science Review Archives, 2025)
This research examines Operation Tracer, a covert British Intelligence initiative during World War II, designed to ensure continuous surveillance in Gibraltar if it were occupied by Axis forces. By embedding a team of operatives within a concealed observation post inside the Rock of Gibraltar, Operation Tracer exemplified the fusion of strategic foresight, technological innovation, and psychological endurance in intelligence planning. Through an analysis of the operation’s design, including threat perception, vulnerability assessment, operational secrecy, and data collection tools, the study demonstrates how Tracer served as a mode for preventive intelligence operations, even though it was never activated. The research further situates Operation Tracer within broader intelligence frameworks by highlighting its contribution to the development of “stay-behind” networks during the Cold War and its symbolic value as a strategic deterrent. Ultimately, this study argues that the true success of Operation Tracer lies not in activation, but in its meticulous planning, which reflects Britain’s wartime ethos of resilience and commitment to maintaining intelligence capabilities in the face of uncertainty